2007
DOI: 10.1016/j.jacc.2007.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Interleukin Family Member ST2 in Patients With Acute Dyspnea

Abstract: Among dyspneic patients with and without acute HF, ST2 concentrations are strongly predictive of mortality at 1 year and might be useful for prognostication when used alone or together with NT-proBNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
155
0
18

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 468 publications
(177 citation statements)
references
References 27 publications
4
155
0
18
Order By: Relevance
“…Concentrations of sST2 are higher in patients with HF than in patients with non-cardiac causes of dyspnoea [42]. However, in many studies comparing sST2 and BNP for HF diagnosis, sST2 was less accurate diagnostically than NT-proBNP.…”
Section: Sst2 and Hf Diagnosis And Prognosismentioning
confidence: 94%
“…Concentrations of sST2 are higher in patients with HF than in patients with non-cardiac causes of dyspnoea [42]. However, in many studies comparing sST2 and BNP for HF diagnosis, sST2 was less accurate diagnostically than NT-proBNP.…”
Section: Sst2 and Hf Diagnosis And Prognosismentioning
confidence: 94%
“…A central role of IL‐33 has been identified in cardiomyocytes protecting against progressive fibrosis and hypertrophy 10. Studies in patients with shortness of breath,11, 12, 13, 14 chest pain,15 and those referred for outpatient echocardiograms16 have shown poorer prognosis among those with higher concentrations of circulating sST2, irrespective of the final clinical diagnosis. Among population‐based studies, the Dallas Heart Study reported increased all‐cause and cardiovascular mortality in younger and middle‐aged adults with greater circulating sST2,17 and there was an increased risk of HF, death, and major cardiovascular events among middle‐aged adults with greater sST2 in the Framingham Heart Study (FHS) 18…”
Section: Introductionmentioning
confidence: 99%
“…In patients with acute heart failure, elevation of ST2 predicts an adverse outcome and is an independent prognostic marker. [146][147][148][149] Interestingly, ST2 predicts an adverse outcome in patients presenting with acute dyspnoea regardless of whether or not they have heart failure 146 and in patients with pulmonary disease. 150 …”
mentioning
confidence: 99%